Bacteriophages as tools in medicine - Hill, Colin (Henry Stewart Talks, 2022)
Introduction to Bacteriophage, The lytic and lysogenic cycle, Phage therapy and antibiotic resistance, Problems using phage in medicine, The Magistral Phage, Phage lysins and endolysins, Using phage to shape the microbiome, Using faecal filtrates, Phage and IBD, Phage as biomarkers of health, Phage and Horizontal gene transfer (HGT) and Antimicrobial resistance (AMR)